Augmented reality in laboratory : perception student on the beneficial surface tension practical during pharmaceutics laboratory session - Manisha Pandey,; Hira Choudhury,; Rohit Kumar Verma,; Mohd Fadzil Zainal Anuar,; Hasnain Zafar Baloch,; Saranyah Shanmugah Nathan,; Tarakini Gunasegaran,; Bhalqish Jeet Kaur Ambar Jeet Singh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Augmented reality (AR) has recently gained much attention in research. AR has the potential to provide flexible timing for learning at any location with new methods and technology. AR technology can enhance class engagement and make it more informative. This study investigated the feedback of Bachelor of Pharmacy (Hons.) and Bachelor of Science (Hons) Pharmaceutical Chemistry (n = 92) in semester two on the use of AR tools in the joint session of pharmaceutics laboratory during surface tension practical. The study questionnaire was developed from literature on AR, and obtained data were analyzed using SPSS 18. According to the collected feedback, 95.6% of the students agreed/strongly agreed that using the AR tool during the practical session was beneficial. Moreover, 94.5% agreed that AR was also helpful after the practical session to recall their learning. 84.8% of the students were found to have a firm agreement with the fact that AR helped to enhance students’ knowledge and practical skills. A large percentage of students (80.4%) strongly agreed that using the AR tool is better than videos for the skill-based session. Most students (88.1%) agreed that the quizzes and information given in the AR tool were beneficial to understanding the practical quickly. The highest percentage of students (90.6%) accepted that the quality of teaching and learning material used in the AR tool was good. The potential of AR use in practical could produce promising outcomes. Effective implementation of AR could improve student engagement, understanding, and learning process on practical skills and could effectively impact the quality of teaching and learning.